2013
DOI: 10.4236/njgc.2013.31001
|View full text |Cite
|
Sign up to set email alerts
|

Coercivity Values Enhancement by Incorporation of Magnetic Powders in Inorganic Matrix Hosts

Abstract: Enhancement in coercivity values of precursor powders of cobalt ferrite embedded in silica xerogel as well as polyaniline was observed using vibrating sample magnetometry. We compared the magnetic properties of pure precursor powders of ferrite cobalt prepared by coprecipitation method and those embedded in xerogel and polyaniline matrix, prepared by sol-gel and by a conventional in situ chemical oxidation polymerization, respectively. The main magnetic effect is the altered coercivity value growing two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…3 and 4) and increases the coercivity. 31 From Table I, magnetic coercivity and squareness of the BaM-PS are significantly larger with respect to other works. [12][13][14][15][16][17] However, M r of the BaM-PS are lower.…”
Section: -5mentioning
confidence: 72%
“…3 and 4) and increases the coercivity. 31 From Table I, magnetic coercivity and squareness of the BaM-PS are significantly larger with respect to other works. [12][13][14][15][16][17] However, M r of the BaM-PS are lower.…”
Section: -5mentioning
confidence: 72%
“…The finding observed in this study corresponds with the one reported by Fang et al [16] in which the authors inferred that the polymer matrix has no significant influence on H c . However, this result is the opposite for hard magnetic particles as reported by Martinez et al [17], as the H c value can be changed by changing the matrix materials that have been embedded with hard magnetic particles. Generally, a small value of H c is preferable in MR materials since this reveals the ability of materials to give a fast response when the magnetising force is given.…”
Section: Samplesmentioning
confidence: 76%
“…In the presence of a magnetic field, the CIPs in the MR foam will experience a magnetic force phenomenon. This magnetic force has an effect on the elasticity of the PU foam [17], thus leading to changes in the PU matrix and the pore shapes as shown in figure 9(b). The deformation reduces the magnetic loss and increases the contact between CIPs, simultaneously enhancing the magnetic field path.…”
Section: Samplesmentioning
confidence: 99%